Assessment of health risk and dose-effect of DNA oxidative damage for the thirty chemicals mixture of parabens, triclosan, benzophenones, and phthalate esters. (December 2022) - Liao, Qilong; Huang, Hehai; Zhang, Xue; Ma, Xiaoju; Peng, Jing; Zhang, Zhaorui; Chen, Chuanying; Lv, Yanrong; Zhu, Xiaohui; Zheng, Jing; Zeng, Xiaowen; Xing, Xiumei; et al.
Abstract: Humans are constantly exposed to parabens (PBs), triclosan (TCS), benzophenones (BPs), and phthalate esters (PAEs) due to the widespread existence of these chemicals in personal care products (PCPs), and the high frequency of usage for humans. Previous studies indicated each class of the above-mentioned chemicals can exhibit potential adverse effects on humans, in particular DNA oxidative damage. However, the health risk assessment of combined exposures to multiple PCPs is limited, especially the overall dose-effect of mixtures of these chemicals on DNA oxidative damage. In this study, we measured the urinary levels of 6 PBs, TCS, 8 BPs, 15 metabolites of PAEs (mono-PAEs), and 8-hydroxy-2′-deoxyguanosine (8-OHdG) from 299 adults simultaneously. PBs, TCS, BPs, and mono-PAEs were frequently detected in urinary samples with median concentrations of 52.888, 0.737, 1.305, and 141.381 ng/ml, suggesting a broad, low-level exposure among participants. Risk assessments indicated approximately 22% and 15% of participants suffered health risks (Hazard index >1) from exposure to TCS and PAEs. The relationship between 8-OHdG levels and chemical exposure was estimated by Bayesian kernel machine regression (BKMR) models. It indicated an overall positive correlation between the mixture of these chemicals and 8-OHdG, with methylparaben and mono-benzyl phthalate contributing the most to this association. Of note, sex-related differences were observed, in which exposure to PCPs led to higher health risks and more pronounced dose-effect on DNA damage in the female population. Our novel findings reveal the health risks of exposure to low-level PCPs mixtures and further point out the overall dose-response relationship between DNA oxidative damage and PCP mixtures. Graphical abstract: Image 1 Highlights: Approximately 22% and 15% of participants suffered health risks from TCS and PAEs. DNA oxidative damage was positively related to the mixture of PBs, TCS, BPs, and PAEs. MeP and MBzP contributed the most to DNA oxidative damage in the mixture. Females suffered a higher health risk and DNA oxidative damage from PCPs exposure.